(untitled) (Journal of the College of Basic Education, 2022)
Population studies are one of the important means to achieve well-being and prosperity for individuals and society, and they have received great attention, especially after the fifties of the last century, as they have gained greater attention at the present time due to their role in planning and development processes. In addition to the interest of geographers, these studies have gained the attention of economists, social workers and politicians